Clinical spectrum of rectal cancer identifies hallmarks of early‐onset patients and next‐generation treatment strategies - Dingcheng Shen; Puning Wang; Yumo Xie; Zhuokai Zhuang; Mingxuan Zhu; Xiaolin Wang; Meijin Huang; Yanxin Luo; Huichuan Yu (Cancer Medicine)
Abstract Background The incidence of colorectal cancer is increasing among young adults and more rectal cancers are reported. This study aimed to identify the clinical features specific for early‐onset rectal cancer and provide insights on cancer management. Methods Early‐onset (<50 years) and late‐onset (≥50 years) rectal cancer patients from a referral tertiary care center (SYSU cohort) and Surveillance Epidemiology and End Results database (SEER cohort) were included to perform a comprehensive comparison on clinical information. Results A total of 552 and 80,341 patients with stages I–III rectal cancer were included in the SYSU and SEER cohorts, respectively. In the SYSU cohort, early‐onset diseases had significantly higher prevalence of family history of cancer and history of HBV infection and lower incidence of comorbidities (p < 0.05). In addition, early‐onset patients presented more frequently with advanced node stage (N2 stage: 16.9 vs. 9.3%, p = 0.017) and high‐risk features, including mucinous or signet cell carcinomas (21.8 vs. 12.9%, p = 0.014), poorly differentiated tumors (28.8 vs. 15.4%, p = 0.002), and perineural invasion (14.5 vs. 7.9%, p = 0.027) compared with late‐onset patients. However, early‐onset patients received more neoadjuvant (18.5 vs. 11.2%, p = 0.032) and adjuvant treatments (71.0 vs. 45.8%, p < 0.001), and they had better overall survival in both SYSU (HR 0.57, 95% CI: 0.34–0.95; p = 0.029) and SEER (HR 0.38, 95% CI: 0.37–0.40; p < 0.001) cohorts. Conclusion Early‐onset rectal cancers are distinct from late‐onset cases in clinicopathological features, treatment modalities, and outcomes. The clinical trials and studies that are specific for young populations are needed to develop optimal strategies for cancer screening, treatment, and surveillance.